Kritik Terhadap Pendekatan Empiris Kajian Keagamaan - Fuad Ramly (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2022)
This article examines the empirical approach in religious studies based on critical and philosophical analyzes. Critical analysis is used to map the strengths and weaknesses of the Empirical Approach, and philosophical analysis to understand the essence of religion. Based on the results of the study it can be described that the Empirical Approach in religious studies or Religious Studies relies on investigations of religious phenomena, as reflected in studies of Sociology of Religion, Anthropology of Religion, Psychology of Religion and so on. In addition to having advantages, the Empirical Approach also has disadvantages. The Empirical Approach is indeed significant for being involved in Religious Studies to evaluate the phenomenon of the diversity of adherents of religions, to build a more noble religious life, but not significant for studying religious beliefs, violence and conflicts in the name of religion as has been done so far. One very important effort in the development of Religious Studies is to realize integration of the Normative Approach and the Empirical Approach in studying religious phenomena. The integration of these two approaches will provide a more comprehensive and philosophical understanding of religion, both existentially (the behavior of believers) and essential (the essence of religion itself). Abstrak Artikel ini mengkaji pendekatan empiris dalam kajian keagamaan berdasarkan analisis kritis dan filosofis. Analisis kritis dipergunakan untuk memetakan kelebihan dan kelemahan Pendekatan Empiris, dan analisis filosofis untuk memahami esensi agama. Berdasarkan hasil kajian dapat dideskripsikan bahwa Pendekatan Empiris dalam kajian keagamaan atau Studi Agama bersandar pada penyelidikan tentang fenomena keberagamaan, sebagaimana tercermin dari kajian-kajian Sosiologi Agama, Antropologi Agama, Psikologi Agama dan sebagainya. Di samping terdapat kelebihan, Pendekatan Empiris juga memiliki kekurangannya. Pendekatan Empiris memang signifikan untuk dilibatkan dalam Studi Agama untuk melakukan evaluasi terhadap fenomena keberagamaan para pemeluk agama, untuk membangun kehidupan beragama yang lebih mulia, tetapi tidak signifikan untuk mengkaji keyakinan keagamaan, kekerasan dan konflik yang mengatasnamakan agama sebagaimana dilakukan selama ini. Salah satu upaya yang sangat penting dalam pengembangan Studi Agama adalah mewujudkan integrasi (keterpaduan) Pendekatan Normatif dan Pendekatan Empiris dalam mengkaji fenomena keagamaan. Integrasi kedua bentuk pendekatan tersebut akan memberikan pemahaman yang lebih komprehensif dan filosofis tentang agama, baik secara eksistensial (perilaku umat beragama) maupun esensial (hakikat agama itu sendiri).